Schistosomiasis in Malaysia. - Chandra Shekhar, K.; Pathmanathan, R. (1987)
Schistosomiasis was discovered in Malaysia in 1975 in an autopsy case. Since 1975 autopsies, surveys, and resurveys have been carried out to identify animal hosts, snail intermediate hosts, and reservoir hosts. Seroepidemiologic tests involving enzyme-linked immunosorbent and circumoval precipitin methods have been used to determine the true incidence and prevalence of this protean disease among the Orang Aslis (aborigines) in Malaysia. With the use of better epidemiologic and parasitologic tools, more cases of schistosomiasis are being reported.